2018
DOI: 10.25073/2588-1108/vnueab.4182
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction in Mobile Service Quality: Evidence from Hanoi and Ho Chi Minh City’s Officers

Abstract: This study explores the factors influencing the quality of telecommunication services in Hanoi and Ho Chi Minh City. By conducting an online survey of 413 office workers, the results indicate that among the five components of the perceived quality of telecommunications services, reliability, assurance, and empathy are Key factors affecting consumer satisfaction in Hanoi and Ho Chi Minh City. The findings of this research help mobile service providers to understand how consumers perceive the quality of mobile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…These findings are in agreement with the findings of Hong and Hai (2018), Flynn et al (2018), Bintu (2017), Mwenda (2017), and Kotler (2015), who carried out studies on the relationship between marketing strategies and sales performance and found a significant relationship. According to Hong and Hai (2018), product quality is the extent to which a product meets the needs of its customer and a firm's product development strategy must therefore focus quality. Flynn et al (2018) also found quality to be an important element in the design and manufacture of products that customers considered superior to those of the competitors, thus increasing sales.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in agreement with the findings of Hong and Hai (2018), Flynn et al (2018), Bintu (2017), Mwenda (2017), and Kotler (2015), who carried out studies on the relationship between marketing strategies and sales performance and found a significant relationship. According to Hong and Hai (2018), product quality is the extent to which a product meets the needs of its customer and a firm's product development strategy must therefore focus quality. Flynn et al (2018) also found quality to be an important element in the design and manufacture of products that customers considered superior to those of the competitors, thus increasing sales.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies indicate a relationship between marketing strategies and sales performance (Bintu, 2017;Chang et al, 2021;Hong & Hai, 2018;Kotler, 2015;Mwenda, 2017;Wawira, 2016). According to Hong and Hai (2018), product quality refers to the extent to which a product meets the needs of its customer and, hence, a product development strategy must be focused on just that.…”
Section: Marketing MIX Strategies and Sales Performancementioning
confidence: 99%
See 1 more Smart Citation
“…M. Lee & Chen, 2014; Shang & Wu, 2017; Wu et al, 2009), which show the stage at which the user achieves what is expected after consumption (Bhattacherjee, 2001). However, there are contextual factors such as perceived risk, trust, efficiency, and functional benefits that could affect m-consumers’ satisfaction levels and impact the continuance use of m-commerce (Hong & Hai, 2018; Rodríguez-Torrico et al, 2019; Wu et al, 2009). Hence, this study integrates perceived risk, trust, efficiency, functional benefits, satisfaction, continuance intentions, and price sensitivity within the ECM for the Indonesian consumer group.…”
Section: Introductionmentioning
confidence: 99%